Editorial: angiogenesis and tumor metastasis - Zhang, Qiang-Zhe; Zhu, Yi-Pan; Rahat, Michal A.; Kzhyshkowska, Julia (Frontiers in oncology, 2023)
Angiogenesis, the process of forming new blood vessels from existing vasculature, allows the delivery of oxygen and nutrients to the tumor and support its progression.Therefore, this necessary process has been recognized as one of the hallmarks of cancer [1], however, its role in promoting and sustaining metastasis is yet not fully elucidated.In cancer, the balance between pro-and anti-angiogenic factors is disrupted in favor of the former, leading to the activation of the "angiogenic switch". Cytokines such as VEGF and its inhibitor TNFSF15 that are secreted from the cells within the tumor microenvironment (TME) participate in the regulation of angiogenesis [2]. Different molecules including protein factors, exosomes and non-coding RNAs can mediate the effect on different cells within the TME and activate signaling pathways that are involved in the process of angiogenesis [3]. The resulting new blood vessels are usually leaky and permeable, and promote the infiltration of immune cells and the progression of the tumor. On the other hand, they can also provide a pathway for the metastatic tumor cells to escape from the primary tumor and reach the circulation, thus supporting metastasis.Metastasis refers to the migration of cancer cells from their primary site to other organs of the body. This process involves requires that the metastatic cell becomes invasive, intravasation into a lymph or a blood vessel, survive in the circulation, and extravasate in the distant organ [4]. These migratory and invasive properties require that the epithelial-to-mesenchymal transition (EMT) process be activated. This allows the metastatic cancer cells to disseminate and enter blood vessels recently formed by angiogenesis. Once the cancer cell is lodged in the new environment, it must undergo the opposite process of mesenchymal-to-epithelial transition (MET) in order re-acquire its ability to proliferate and colonize the distant sites, which is necessary to form a metastatic, secondary tumor in the distant organ [5]. Another